Mountain garlic (Allium lusitanicum Lam., Amaryllidaceae) – new neglected aboriginal species for Belarusian flora - Dzhus, Maxim A.; Tikhomirov, Valery N. (Experimental Biology and Biotechnology, 2019)
Mountain Garlic (Allium lusitanicum Lam., Amaryllidaceae J. St.-Hil.) is indicated for the first time as an aboriginal species for the Belarusian flora. According to the own and herbarium data A. lusitanicum was collected in the southwestern part of the Belarus (Brest district, Brest region). For the long time this species was determinated by Belarusian botanists as A. angulosum L. Brief information about the nomenclature, systematics of the onions close to A. senescens s. l., phytocenology, ecological and biological features, diagnostic differences of A. lusitanicum from morphologically similar species is given. New localities clarify the total distribution of A. lusitanicum in Eastern Europe.